FAKTOR-FAKTOR EKOLOGIS HABITAT LARVA NYAMUK ANOPHELES DI DESA MUARA KELANTAN KECAMATAN SUNGAI MANDAU KABUPATEN SIAK PROVINSI RIAU TAHUN 2009 - Ernamaiyanti Ernamaiyanti; Adnan Kasry; Zainal Abidin (Program Pascasarjana Universitas Riau, 2010)
Malaria is a disease caused by Plasmodium parasites. Year 2007 people infected with malaria District Sungai Mandau 57.37 per 1000 population. This study aims to determine ecological factors that affect the habitat of the Anopheles mosquito larvae in the village of Muara Kelantan District Sungai Mandau, Siak Regency in 2009. Depth of water, water flow, mud bottom, thecolor of brown waters, and temperature, salinity, pH water,and humidity on the waters in the village of Muara Kelantan suited for the life of the larvae of Anopheles spp. This is supported bythe density of mosquito larvae of Anopheles spp calm in the gutter, the gutter flow and swampland in succession 0,006 ind/ml, 0,078 ind/ml, and 0,004 ind/ml respectively.